Conocimientos y prácticas en relación al autoexamen de mama en las adjudicatarias de los puestos del Mercado la Tebaida de la ciudad de Loja. - Montaño Molina, Mónica Vanessa (2016)
Breast cancer is the most common in women in both developed and developing countries in cancer; does not discriminate age, race, or social status, no woman is free of suffering, usually it is usually diagnosed in advanced stages, but if there is an early diagnosis can be started early treatment. In Ecuador breast cancer represents a major public health problem. Each year 1,500 new cases occur, according to the Ministry of Public Health. Breast self-examination is a useful for detecting breast abnormalities tool. This research aims to investigate what knowledge and practices related to breast self-examination in the winning of the market stalls Tebaida City Loja. It was conducted under a descriptive, transversal and prospective approach. a survey, comprising 16 items was used, and determine which value the knowledge and practice of breast self-examination, the sample consisted of 50 women selected according to inclusion and exclusion criteria, which they were surveyed and where the following results were obtained: 74% of women have adequate knowledge and 26% have inadequate knowledge; 80% do not practice breast self-examination, 20% of the population if you practice. So it was concluded that although there is adequate knowledge is a poor practice by the population studied. Keywords: women, breast self-examination, knowledge, practices.